The use of mid-arm circumference for the estimation of adult body weight: A post mortem computed tomography approach. (September 2020) - Nathongchai, Raksachai; Rutty, Jane; Brough, Alison; Aljanaahi, Nayef; Morgan, Bruno; Rutty, Guy
Highlights: The study translates a pre-hospital method for estimating an adult's body weight from the mid upper arm circumference to post mortem computed tomography. The method showed a strong relationship between mid-arm circumference and post mortem body weight. The mid-arm circumference measurement method using post mortem computed tomography yielded excellent intra- and inter-observer reliability. The quick, easy and cost-effective post mortem computed tomography technique to estimate adult body weight may be useful if weighing equipment is unavailable or the body is incomplete. Abstract: Purpose: Cadaver body weight (BW) is to be documented, where possible, in all forensic autopsy examinations. However, it may not always be possible to ascertain an accurate BW if, for example, functioning weighing equipment is unavailable or the body is incomplete. This research aimed to translate an adult clinical prehospital method which uses a mid-arm circumference (MAC) measurement to estimate BW to establish a post mortem computed tomography (PMCT) technique for adult cadaver BW estimation. Method: The clinical method was adapted for PMCT bone and soft tissue methods. Right and left MAC measurements were obtained by four independent observers from sixty-six (45 males and 21 females) consented research adult PMCT scans using the Osirix DICOM viewer. All observers rated MAC quality score on each arm from 0 (very poor) to 3 (good). Results: In the final group of fifty-five with MAC quality score ≥ 1, MAC measurements correlated well with actual BW ( r =0.87) and yielded excellent intra- and inter-observer reliability. There were no statistical differences between the two MAC methods, sexes or side of arm. Mean estimated BW by previous study Equation, BW=(4×MAC)-50, was 0.47 kg greater than mean actual BW with limits of agreement of 12.7 kg; this would be reduced to 9.2 kg if an outlier were excluded. Conclusions: The study identifies a quick and easy PMCT technique to estimate adult BW using PMCT. However, the result remains only an estimation and caution should be expressed if a result is applied to medico-legal cases.